1992
DOI: 10.1148/radiology.183.2.1561334
|View full text |Cite
|
Sign up to set email alerts
|

Chiari I malformations: clinical and radiologic reappraisal.

Abstract: Clinical findings and magnetic resonance (MR) images in 68 patients with Chiari I malformations were retrospectively analyzed to identify those radiologic features that correlated best with clinical symptoms. A statistically significant (P = .03) female predominance of the malformation was observed, with a female: male ratio of approximately 3:2. Associated skeletal anomalies were seen in 24% of patients. Syringomyelia was detected in 40% of patients, most commonly between the C-4 and C-6 levels. Of the 25 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
238
5
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 454 publications
(265 citation statements)
references
References 0 publications
6
238
5
5
Order By: Relevance
“…This contrasts with the normal position of the cerebellar tonsil as reported in the literature (1±1.9 mm above the foramen magnum) [3]. This degree of tonsillar ectopia falls below the threshold consistent with the radiological diagnosis of the Chiari type 1 malformation [3,21,38]. In 20% of our patients, a radiological diagnosis of the Chiari 1 malformation was made based on tonsillar ectopia in excess of 5 mm, the accepted radiological standard.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…This contrasts with the normal position of the cerebellar tonsil as reported in the literature (1±1.9 mm above the foramen magnum) [3]. This degree of tonsillar ectopia falls below the threshold consistent with the radiological diagnosis of the Chiari type 1 malformation [3,21,38]. In 20% of our patients, a radiological diagnosis of the Chiari 1 malformation was made based on tonsillar ectopia in excess of 5 mm, the accepted radiological standard.…”
Section: Discussioncontrasting
confidence: 59%
“…In fact, a recent publication reported that some patients with the Chiari 1 malformation had been previously diagnosed with fibromyalgia [38]. The symptoms common to these disorders include pain, headache, clumsiness, grip weakness, instability of gait, dizziness, paresthesiae and numbness [1,18,19,21,38]. Cognitive impairment, including short-term memory loss and difficulty with concentration (commonly referred to as "fibro fog" among fibromyalgia patients), has also been reported by patients with the Chiari 1 malformation [38].…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Chiari-I malformation may remain asymptomatic or may present with few clinical ®ndings due to brain stem compression or cervical syringomyelia. 15 Usually, Chiari-I malformation is acquired, and rarely hereditary. Acquired Chiari-I malformation may be due to a cerebral mass lesion such as tumour, cerebral oedema and hydrocephalus, lumbar-peritoneal shunt or trauma.…”
Section: Discussionmentioning
confidence: 99%
“…139 Lower position of the cerebellar tonsils in CM is associated with a greater likelihood of syringomyelia. [139][140][141] It is probable that Chiari symptoms and the formation of spinal syringes are the result of crowding at the foramen magnum that leads to abnormal movement of CSF at the craniocervical junction. 134 Children with CM often have a smaller than normal posterior fossa volume, resulting in crowding of the posterior fossa and foramen magnum contents.…”
Section: Chiari and Syringomyeliamentioning
confidence: 99%